UV Sensor Based on Fiber Bragg Grating Covered with Graphene Oxide Embedded in Composite Materials - Piotr Lesiak; Karolina Bednarska; Krzysztof Małkowski; Łukasz Kozłowski; Anna Wróblewska; Piotr Sobotka; Kamil Dydek; Anna Boczkowska; Tomasz Osuch; Alicja Anuszkiewicz; Wojciech Lewoczko-Adamczyk; Henning Schröder; et al. (Sensors, 2020)
Polymer–matrix composites degrade under the influence of UV radiation in the range of the 290–400 nm band. The degradation of polymer–matrix composites exposed to UV radiation is characterized by extensive aging of the epoxy matrix, resulting in deterioration of their mechanical properties. Glass fibers/epoxy resin composites were made by an out-of-autoclave method whereas a fiber optic sensor was placed between different layers of laminates. In our work, we used a fiber Bragg grating sensor covered with graphene oxide and embedded in a polymer matrix composite to monitor UV radiation intensity. Measurements of UV radiation may allow monitoring the aging process of individual components of the polymer composite. In order to estimate the number of microcracks of epoxy resin, microstructure observations were carried out using a scanning electron microscope.